When Place is Too Big: Happy Town and Unhappy Metropolis - Okulicz-Kozaryn Adam (European Regional Science Association (ERSA), 2015)
Most scholars in urban studies, public policy and public administration support city living, that is, they (usually implicitly) suggest that people are happy in cities or at least they focus on how to make people happy in cities. Planners also largely focus on making cities happy places, e.g., so called Smart Growth. In short, low density living is not a popular idea among scholars, although it used to be several decades ago. This study uses General Social Survey to calculate subjective well-being (happiness) by size (population) of a place to find out when a place is too big. The answer is somewhere between 200 and 700 thousand of people. When population exceeds several hundred thousand, the unhappiness settles in. Results are robust to the operationalization of an urban area, and to the elaboration of the model with multiple controls known to predict life satisfaction. This study concerns only the US, and results should not be generalized to other countries. Directions for future research are discussed.
Keywords: 330